STRONG CHANGES OF THE PHOTOMETRIC BEHAVIOUR OF CARBON MIRAS - Marsakova, V. I. (Одеські астрономічні публікації, 2017)
Analysis of variations of the light curves parameters of 16 Miras of spectral classes C and S has been made. A number of the peculiarities of these variations has been found. One of the most interesting results is the detection of the mean brightness variations: they are cyclic (with a superperiod of about 10 Х P0 and not stable cycle length) or secularly decreasing.